Pengaruh Kompensasi dan Stres Kerja Terhadap Kinerja Karyawan pada Perum Damri - Nurhayati Nurhayati (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
The ups and downs of employee performance are due to the presence of co-workers lack of support, unpleasant bosses and demanding employees against benefits that are not met by the company. Condition This makes it difficult for the company to grow rapidly. This research aims to determine the effect between compensation and work stress on employee performance both simultaneously and partially. This research was conducted at Perum Damri Cabang Lampung Branch This study consists of independent variables, namely compensation and work stress, and the dependent variable is employee performance. Number of samples used in this study amounted to 42 respondents using the method slovine sample. Hypothesis testing was carried out using the Multiple method Regression (Multiple Regression) . Data analysis using software SPSS statistics 20.0. The results of this study show in the F test (simultaneous) that compensation and work stress have a positive and significant effect on employee performance with a sig F value of 0.000 <0.05 and Fcount of 66.041. The results of the t (partial) test of compensation have a positive effect and significant to employee performance with a sig t value of 0.003 < 0.05 and tcount value is 3.163, while work stress has no significant effect with a sig t value of 0.937 > 0.05 and the tcount value is 0.079. So it can be concluded that only variables compensation that has a significant effect on employee performance while the work stress shows the opposite result.